2021
DOI: 10.1002/cnr2.1461
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional study of psychosocial well‐being among lesbian, gay, bisexual, and heterosexual gynecologic cancer survivors

Abstract: Background: Delays in care and increased risk for mental health diagnoses put individuals identifying as a sexual minority with cancer at risk for decreased quality of life.Aim: To assess psychosocial health among sexual minority gynecologic cancer survivors, we compared self-reported quality of life and psychosocial measures between individuals diagnosed with gynecologic cancers identifying as lesbian/gay/ bisexual (LGB) and heterosexual.Methods and Results: English-speaking adults with gynecologic cancers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…For example, a study of sexual minority breast cancer survivors ( 43 ) recorded clinically relevant depression and anxiety in 31% and 25% of participants respectively. A study of LGB people with gynecological cancer ( 17 ) reported depression and anxiety in 32% at 25% of participants respectively; and clinical levels of distress were reported by 13.7% of participants in a study of gay and bisexual men with prostate cancer ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study of sexual minority breast cancer survivors ( 43 ) recorded clinically relevant depression and anxiety in 31% and 25% of participants respectively. A study of LGB people with gynecological cancer ( 17 ) reported depression and anxiety in 32% at 25% of participants respectively; and clinical levels of distress were reported by 13.7% of participants in a study of gay and bisexual men with prostate cancer ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cisgender breast cancer survivors who identify as lesbian, bisexual or queer (LBQ), report higher levels of distress and lower quality of life than heterosexual women ( 1 , 15 , 16 ). There is also some evidence that LBQ women with gynecological cancer report significantly higher rates of depression, anxiety and post-traumatic stress disorder ( 17 ), than their heterosexual counterparts. A national survey including a range of cancer types reported higher rates of poor self-reported health in lesbian women and higher rates of psychological distress in bisexual women, compared to heterosexual women ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, as with prior caregiving research, SGM participants were more likely to report previous mental health diagnoses and higher life course stress scores than non‐SGM participants 35 . The fact that SGM participants experienced PTG equally could therefore suggest resilience and warrants future research.…”
Section: Discussionmentioning
confidence: 52%
“…In this study, as with prior caregiving research, SGM participants were more likely to report previous mental health diagnoses and higher life course stress scores than non-SGM participants. 35 The fact that SGM participants experienced PTG equally could therefore suggest resilience and warrants future research. While small in magnitude, each dyad member's higher life course stress predicted their lower wellbeing, patients' higher life course stress predicted partners' lower wellbeing, but partners' life course stress did not predict patients' lower wellbeing.…”
Section: Hypothesis 3 Resultsmentioning
confidence: 99%
“…Although there are support groups for men with prostate cancer, gay and bisexual men did not always feel included in these groups leaving their needs unmet [13]. Although there are support groups for SGD cancer patients, a study found that only 21% of patients knew about these groups, but 81% of those that knew about these resources used them [14].…”
Section: Resultsmentioning
confidence: 99%